2021
DOI: 10.35848/1882-0786/ac0fb8
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced light extraction efficiency of micropixel geometry AlGaN DUV light-emitting diodes

Abstract: We report a 1.8 times improved light extraction efficiency for truncated cone AlGaN DUV (275 nm emission) micropixel LEDs when the pixel size was reduced from 90 to 5 μm. This is a direct consequence of reducing the re-absorption of sideways-travelling photons, as the lateral absorption length was measured to be 15 μm using cathodoluminescence. We also investigated the effect of an Al2O3/Al sidewall coating on the device performance which led to an on-wafer pulsed-mode brightness of 10.3 kW cm−2 from a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 37 publications
(46 reference statements)
1
24
0
Order By: Relevance
“…Here we summarize the EQE of AlGaN micro-LEDs and conventional LEDs in the UV spectral range (200-400 nm), see Fig. 2 [13,14,[18][19][20][21][22][23][24][25][26][27]. To date, most researches mainly focus on the diverse applications of UV micro-LEDs, but relatively few works have investigated the improvement of EQE achievable with UV micro-LEDs.…”
Section: A Current State Of the Art And Challenges Of Uv Micro-ledsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here we summarize the EQE of AlGaN micro-LEDs and conventional LEDs in the UV spectral range (200-400 nm), see Fig. 2 [13,14,[18][19][20][21][22][23][24][25][26][27]. To date, most researches mainly focus on the diverse applications of UV micro-LEDs, but relatively few works have investigated the improvement of EQE achievable with UV micro-LEDs.…”
Section: A Current State Of the Art And Challenges Of Uv Micro-ledsmentioning
confidence: 99%
“…In the UVC band, researchers in University of Science and Technology of China (USTC) fabricated UV LEDs emitting at ∼275 nm with different sizes of 300, 200, 100, 50, and 20 µm and they found that the peak EQE of a 20 µm micro-LED with a value of 1.2%, increased by 20% compared to that of a 300 µm micro-LED [13]. Also, University of South Carolina (USC) has reported a 5 µm micro-LED with a record brightness of 570 Wcm −2 and the peak EQE is ∼2% [18]. At present, for a conventionally sized LED in the UVC region, RIKEN has reported a record high EQE of ∼20% for UVC LED emitting at 275 nm [20].…”
Section: A Current State Of the Art And Challenges Of Uv Micro-ledsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 As the R/G/B QDs show higher absorption efficiency to lower wavelength photons, blue-violet and near-UV micro-LEDs were proposed to improve the color rendering and increase the excitation efficiency. 11,12 While the research on AlGaN-based deep-ultraviolet (deep-UV) micro-LEDs is still challenging, 13,14 few efforts were invested in its application as an excitation source to R/G/B QDs. 15 In this work, we focused on the AlGaN-based deep-UV micro-LED as a high-efficiency excitation source for QD display.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, various electrode structures, such as Ni/Mg [8], mesh p-GaN/ITO [12], Mo/Al [13], and Cu nanowires [14] have been used to solve the issues related to ohmic contact with the p-(Al)GaN layer while minimizing DUV light absorption through the electrode. In addition, device structures have been redesigned using AlN/h-BN heterostructures [1], GaN/AlN quantum-disk nanorods [15], Graded AlGaN alloy structures [16], wavy quantum well [17], UVB micro-LED [18], and micropixel DUV LED [19] to further improve the quantum efficiencies of DUV LEDs. Despite these efforts, the EQE values of AlGaN-based top-emitting DUV LEDs (even with tunnel heterojunctions) reported thus far do not exceed 2.8% [20]- [24].…”
Section: Introductionmentioning
confidence: 99%